Assessment of the genetic changes of the attenuated Hanvet1.vn strain compared with original virulent 02HY strain of the porcine reproductive and respiratory syndrome virus - Thi Nga, Nguyen; Thu, Ha Thi; Hoa, Nguyen Thi; Hien , Vu Thi; Thu Trang, Nguyen; Thanh Ba, Nguyen; Van Khanh, Tran; Huu Vu, Nguyen; Van Quyen, Dong; Long Thanh, To; Duy Khang, Dinh (Vietnam Journal of Biotechnology, 2022)
The attenuated porcine reproductive and respiratory syndrome virus (PRRSV) strain Hanvet1.vn was developed by Hanvet Pharmaceutical Co., Ltd. by inoculating the virulent strain 02HYon Marc-145 cells for 80 generations and used to produce PRRS vaccine. In this study, we published the results of sequencing, analyzing and comparing the genome of the attenuated PRRSV strain Hanvet1.vn compared with the original pathogenic strain 02HY. The genomes of strains Hanvet1.vn and 02HY have 8 reading frames, coding for 8 non-structural and structural proteins: NSP1a, NSP1b, GP2, GP3, GP4, GP5, MP, NP. After sequencing and translating into proteins, the gene sequence of each open reading frame (ORF) of strain Hanvet1.vn was compared with the sequence of pathogenic strain 02HY to find nucleotide and amino acid changes. The results showed that the Hanvet1.vn pathogenic strain genome (Genbank Accession KU842720) when compared with the pathogenic strain 02HY genome (Submission2490633) had89 nucleotide mutations that changed 51 amino acids in 7 ORFs and 7 proteins, respectively. Particularly, ORF6 encoding for the M protein is completely unchanged. The size of each reading frame is also exactly the same. It showed that there were no insertion and deletion (Indel) mutations in the ORFs of the attenuated strain after 80 generations of inoculation. There was a change in the genome that made the strain Hanvet1.vn become attenuated, but the gene encoding for the GP5 protein that induces the production of neutralizing antibodies only changed two nucleotides at position 471 (A->G), causing the TCA codon to turn into a TCG codon. This is a silent mutation and both codons code for the amino acid Serine (S). The second mutation at position 587 (A->T) causes Glutamine (Q) to transform into Leucine (L). However, this modification does not belong to the GP5 antigenic epitopes. In clonclusion, after 80 passages, despite changes occurred in genes of Hanvet1.vn strain for becoming an attenuated strain, the GP5 protein of the attenuated strain did not change its antigenic amino acids.